A Responsive Approach to Organizational Misconduct: Rehabilitation, Reintegration, and the Reduction of Reoffense. Issue 3 (July 2014) - Bertels, Stephanie; Cody, Michael; Pek, Simon
ABSTRACT: In this article, we examine how regulators, prosecutors, and courts might support and encourage the efforts of organizations to not only reintegrate after misconduct but also to improve their conduct in a way that reduces their likelihood of re-offense (rehabilitation). We explore a novel experiment in creative sentencing in Alberta Canada that aimed to try to change the behaviour of an industry by publicly airing the root causes of a failure of one the industry's leaders. Drawing on this case and prior work, we articulate a model for a responsive and restorative approach to organizational misconduct that balances the punitive role of regulators and courts with new roles in supporting and overseeing rehabilitation.